1986
DOI: 10.2134/agronj1986.00021962007800020011x
|View full text |Cite
|
Sign up to set email alerts
|

Quality and Yield Response of Four Warm‐Season Lawngrasses to Shade Conditions1

Abstract: Warm-season turfgrasses differ widely in their tolerance to low light. Shade conditions, as the result of shrub or tree presence, are greatly influenced depending on whether the tree or shrub is deciduous or evergreen in nature. The purpose of this study was to determine the influence of deciduous shade on the quality and yield of four major warm season lawngrasses. Zoysiagrass (Zoysia japonica (Stued.) X Z. tenuifolia (Willd.) 'Emerald'], St. Augustinegrass (Stenotaphrum secundatum (Walt.) Kuntze] 'Fioratam' … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 2 publications
1
17
0
Order By: Relevance
“…Turf visual color score differed as a result of shade with the highest visual color score at 30% shade and lowest scores at 70% shade (Table 3). Similar responses to shade for turf visual quality score had been reported (Barrios et al, 1986;Qian and Engelke, 2000;Trenholm and Nagata, 2005). Turf visual quality was varied in response to K rate.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…Turf visual color score differed as a result of shade with the highest visual color score at 30% shade and lowest scores at 70% shade (Table 3). Similar responses to shade for turf visual quality score had been reported (Barrios et al, 1986;Qian and Engelke, 2000;Trenholm and Nagata, 2005). Turf visual quality was varied in response to K rate.…”
Section: Resultssupporting
confidence: 52%
“…In both trials, shoot DW of 'Captiva' differed in response to shade with the highest DW at 30% shade and lowest at 70% shade (Tables 1 and 3). This is similar to results reported by Trenholm and Nagata (2005) for st. augustinegrass, 'Bitter Blue', 'Floratam', 'Palmetto', 'Seville', and the experimental line 1997-6 and Barrios et al (1986), who reported that clipping yield of 'Floratam' and 'Floratine' generally decreased with increasing shade. Allard and Nelson (1991) reported that dry matter production of tall fescue was reduced at low irradiance (70% shade) as a result of fewer tillers per plant with no shoot growth response to K rate.…”
Section: Resultsmentioning
confidence: 99%
“…are documented as shade-tolerant species (Ervin et al, 2002;Trenholm et al, 2004;Qian and Engelke, 2008). had better shade tolerance than 'Floratam' St. Augustinegrass, as indicated by higher quality ratings and clipping yields (Barrios et al, 1986). had better shade tolerance than 'Floratam' St. Augustinegrass, as indicated by higher quality ratings and clipping yields (Barrios et al, 1986).…”
mentioning
confidence: 97%
“…It is likely that the fertilizer nutrients were almost or completely lost from the root zone of the re‐invading stolons due mainly to the high rainfall in late May (days 17–27; Table 2), although the present study was able to confirm this as late as at the end of the experiment (Table 3). Furthermore, the non‐significant effect of the −L treatment may be explained by the fact that centipedegrass has good tolerance to low light (Barrios et al. 1986; Islam and Hirata 2005b).…”
Section: Discussionmentioning
confidence: 99%